The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations THE NEW HOME HOMELY HINTS ON HEALTH Cleanliness is the family's first home rule, for cleanliness is the first law of health, and health is essential to happiness. Household dirt (including dust) is dangerous to health and the home must be kept as free from it as possible. A child will always remember the lessons of a clean home. ON LIGHTING Bad lighting favours a poor standard of cleanliness. Arrange tables, etc., so as to get a good light from the windows. Hang window curtains well back, and if you have light inner curtains, keep them very clean. Clean windows weekly, or oftener if they get dull. [illustration] Keep curtains away from the windows. If electricity is available, sufficiently powerful lamps should be placed in the most advantageous positions for reading and sewing, with the light coming over the left shoulder on to the book or work. Have electric lamps fixed in dark cupboards and on dim staircases — a safeguard against breakages and falls. Electric light need not give any glare to the eyes, and it is well to note that it does not in any way pollute the air you breathe, which should be kept as clean and pure as possible. To ensure clear light, use lamp shades which can be easily washed with soap and water. [illustration] Take care of your eyes. 3 177/5/8/2